Association between the TCF7L2 rs12255372 (G/T) gene polymorphism and type 2 diabetes mellitus in a Cameroonian population: a pilot study. Issue 1 (23rd April 2015) - Nanfa, Dieudonne; Sobngwi, Eugene; Atogho‐Tiedeu, Barbara; Noubiap, Jean Jacques N; Donfack, Olivier Sontsa; Mofo, Edith Pascale Mato; Guewo‐Fokeng, Magellan; Nguimmo Metsadjio, Aurelie; Ndonwi Ngwa, Elvis; Pokam Fosso, Priscille; Djahmeni, Eric; Djokam‐Dadjeu, Rosine; et al.
Abstract: Background: To study the relationship between the rs12255372 (G/T) polymorphism of the transcription factor 7‐like 2 ( TCF7L2 ) and type 2 diabetes mellitus (T2DM) in a Cameroonian population. Methods: This case–control study included 60 T2DM patients and 60 healthy normoglycemic controls, all unrelated and of Cameroonian origin, aged above 40 years (range 40–87). The Restriction Fragment Length Polymorphism ‐ Polymerase Chain Reaction (RFLP‐PCR) was used for genotyping. Results: The T allele frequency was significantly higher in the diabetic group (0.44) than in the control group (0.17). This allele was significantly associated to a greater risk of developing T2DM as compared to the G allele (OR = 3.92, 95% CI 2.04 – 7.67, p < 0.0001). The codominant (additive) model explained best the risk of developing the disease, as the TT genotype was significantly associated to T2DM when compared to the GG genotype (OR = 4.45, 95% CI 1.64 – 12.83, p = 0.0014). By logistic regression adjusted for age, this OR was 4.33 (95% CI: 1.57 – 11.92, p = 0.005). Conclusion: Our findings suggest that the rs12255372 (G/T) polymorphism of the TCF7L2 gene is an important risk factor for T2DM in the Cameroonian population.